Trends of Late Presentation to Care in Patients with Chronic Hepatitis C during a 10-Year Period in Croatia - Neven Papic; Leona Radmanic; Davorka Dusek; Ivan Kurelac; Snjezana Zidovec Lepej; Adriana Vince (MDPI AG, 2020)
Late presentation to care is the major obstacle to receiving treatment for chronic hepatitis C (CHC). Our aim was to analyze the prevalence and trends of late presenters (LP) at first consultations in Croatia during a 10-year period. This retrospective cross-sectional study included all adult CHC patients (n = 854) entering specialist medical care at the University Hospital for Infectious Diseases Zagreb between 2009 and 2018. LP was defined as liver stiffness measurement ≥ 9.5 kPa or biopsy METAVIR F ≥ 3. During the study period, mean patients' age increased from 37 to 52 years while HCV genotype distribution changed leading to the replacement of genotype 1b with 1a (g1b 32% to 21%; g1a 19% to 38%). A total of 320 (37.4%) were LP; they were older (47.5, IQR 40.5-57.6), and more commonly infected with g1b (34.1%) and g3 (42.5%). The prevalence of LP significantly increased from 31.9% in 2009 to 46.5% in 2018. Late presentation for care of CHC is increasing in Croatia suggesting a gap of diagnosing strategies in patients over 50 years.